KAJIAN INDEKS KEPUASAN INSAN OMBUDSMAN PENGGUNA LAYANAN PERPUSTAKAAN TERHADAP LAYANAN PERPUSTAKAAN OMBUDSMAN REPUBLIK INDONESIA KURUN WAKTU 2019-2020 - Damaji Ratmono (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2020)
This study discusses the Ombudsman Satisfaction Index for users of library services for the Ombudsman library service for the period of 2019 to 2020. This study will aim to find out and analyze the ombudsman index of satisfaction for library services in the Indonesian Ombudsman library so that the Ombudsman library can create strategies to increase the satisfaction of visitors, especially from the ombudsman.This study uses a qualitative method approach with measurements using a Likert Scale developed by the Ministry of Administrative Reform and Bureaucratic Reform of the Republic of Indonesia Number 14 of 2017 concerning Guidelines for the Preparation of a Public Satisfaction Survey for Public Service Providers. Questionnaires were distributed in a way that was distributed online (e-survey) to the Ombudsman as users of the Ombudsman library. Determination of the number of respondents was chosen based on the Morgan and Krejcie Sample table contained in the guidelines for the preparation of the public satisfaction survey of public service delivery units No. 14 of 2017 published by Kemenpan RB, so that the total number of visitors from the ombudsman people at their headquarters in Jakarta is as much as an average of 100 people per year, the number of samples obtained is as many as 80 respondents.In this study, the results of the Ombudsman Community / People Satisfaction Index for library services at the RI Ombudsman library are getting a good category with a value of 3.23 or if converted to 80.63.In this study, there are two service elements that get the highest value, namely the service cost/tariff element that gets a value of 3.96 or 99.06 and the behavioral element of an officer or librarian who gets a value of 3.46 or 86.56. Whereas the service element that gets the lowest value is the facility and infrastructure element with a value of 2.80 or 70.00 and the product element specification type of service that is with a value of 2.89 or 72.19. From the results of this survey, it is concluded that for the future service program, the Ombudsman library must carry out its service improvement activities to comply with specific library service standards and increase the budget in improving existing facilities and infrastructure so that service quality can run more optimally.